Magyarország csatlakozása a háromhatalmi egyezményhez - Olasz, Lajos (Közép-Európai Közlemények, 2016)
On 27th September, 1940, Germany, Italy, and Japan signed the tripartite pact. Hungary announced it immediately that it wanted to join the alliance. The Hungarian Government hoped to keep Germany away from Hungarian internal affairs and prevent Hitler’s raising the extreme right to power. On the other hand, the Government wanted to gain support from the Axis powers to get back all the Hungarian territories that had been detached in Trianon. For Berlin, expansion was important in order to gain control over the Balkans. On 20th November, Hungary joined, then in the following days Romania and Slovakia also joined. In order to counterbalance this Pact, Pál Teleki made efforts to improve the relationship with neutral Yugoslavia. With this joining, the Hungarian Government eventually committed itself to the Axis powers. In return, however, it could only strengthen its positions a bit compared to the local extreme right.